A voltage-pulse-modulated giant magnetoresistance switch with four flexible sensing ranges. (22nd September 2021) - Liu, Mengli; Du, Wei; Su, Hua; Liu, Bo; Meng, Hao; Tang, Xiaoli
Abstract: This article introduces an innovative technique for achieving a giant magnetoresistance (GMR) switch with an adjustable sensing field range. A spin-valve (SV) patterned into a strip shape is grown on a specific (110)-cut Pb(Mg1/3 Nb2/3 )0.7 Ti0.3 O3 (PMN-PT) substrate. In the process of depositing films, a magnetic easy axis of the free layer in the SV is produced along the [001] direction (the x -axis) of the PMN-PT. This PMN-PT can produce a nonvolatile strain by using a positive voltage pulse. Accordingly, the magnetic moment of the free layer can be modulated to the y -axis by the strain-mediated magnetoelectric coupling effect produced in the SV/PMN-PT heterostructure. Furthermore, a negative voltage pulse can release the strain and revert the magnetic moment to the initial [001] direction. The effective field along the [1-10] direction produced by the nonvolatile strain can modulate the easy axis of the free layer, changing it from the x -axis to the y -axis. Therefore, large and small switching fields are achieved in a bipolar GMR switch. Furthermore, by applying positive and negative voltage pulses at appropriate moments, two asymmetrical switching field ranges are obtained. Thus, a GMR switch with four adjustable switching field ranges can be obtained. The proposed modulating model is flexible and can meet the requirements of specific and different application systems. The proposed design reveals a great potential for the application to the internet of things and the development of low-power and high-efficient magnetoresistive sensors.